Fine analysis of genetic diversity of the tpr gene family among treponemal species, subspecies and strains. - Arturo Centurion-Lara; Lorenzo Giacani; Charmie Godornes; Barbara J Molini; Tara Brinck Reid; Sheila A Lukehart (Public Library of Science (PLoS), 2013)
The pathogenic non-cultivable treponemes include three subspecies of Treponema pallidum (pallidum, pertenue, endemicum), T. carateum, T. paraluiscuniculi, and the unclassified Fribourg-Blanc treponeme (Simian isolate). These treponemes are morphologically indistinguishable and antigenically and genetically highly similar, yet cross-immunity is variable or non-existent. Although all of these organisms cause chronic, multistage skin and systemic disease, they have historically been classified by mode of transmission, clinical presentations and host ranges. Whole genome studies underscore the high degree of sequence identity among species, subspecies and strains, pinpointing a limited number of genomic regions for variation. Many of these "hot spots" include members of the tpr gene family, composed of 12 paralogs encoding candidate virulence factors. We hypothesize that the distinct clinical presentations, host specificity, and variable cross-immunity might reside on virulence factors such as the tpr genes.Sequence analysis of 11 tpr loci (excluding tprK) from 12 strains demonstrated an impressive heterogeneity, including SNPs, indels, chimeric genes, truncated gene products and large deletions. Comparative analyses of sequences and 3D models of predicted proteins in Subfamily I highlight the striking co-localization of discrete variable regions with predicted surface-exposed loops. A hallmark of Subfamily II is the presence of chimeric genes in the tprG and J loci. Diversity in Subfamily III is limited to tprA and tprL.An impressive sequence variability was found in tpr sequences among the Treponema isolates examined in this study, with most of the variation being consistent within subspecies or species, or between syphilis vs. non-syphilis strains. Variability was seen in the pallidum subspecies, which can be divided into 5 genogroups. These findings support a genetic basis for the classification of these organisms into their respective subspecies and species. Future functional studies will determine whether the identified genetic differences relate to cross-immunity, clinical differences, or host ranges.